Intra-Stromal Corneal Ring Segments - Ramendra Bakshi; Charu Khurana; Ritika Sachdev; Mahipal Sachdev (Delhi Journal of Ophthalmology)
Intra-stromal corneal ring segments (ICRs) are a new modality in the treatment of corneal ectactic disorders like keratoconus, post lasik ectasia and pellucid marginal degeneration. ICRS is a minimally invasive technique wherein the central optical zone is not disturbed with long term convenient refractive correction. Two brands of ICRS segments are popular commercially, Intacs (Additions Technology Inc) and Ferrara Rings. ICRS reduces the sphere, cylinder and the spherical equivalent in keratoconus. Pre-operative evaluation and patient selection plays a key role in the success of the implant. The determination of which segment to implant depends upon pre-operative manifest refraction, spherical equivalent, location of the cone and degree of asymmetric astigmatism. ICRS along with collagen cross linking has opened new vistas in the treatment of keratoconus and corneal ectasia. While cross linking stops the progression of the ectasia and reverses it to some extent, ICRS flatten or normalize the corneal shape. Combining both the modalities together has a synergistic action and can be performed simulatneously or sequentially. Complications are rare as ICRS implantation is reversible, no corneal tissue is removed, and the central optical zone is not invaded.